Using Some of Quality Techniques in Supply Chain Management to Improve the Production Processes - Nagham Yousif Abidalreda; Sura Adnan Jawad (International Journal of Supply Chain Management, 2019)
Abstract- The research tackled the problem of lowing the level of Supply chain quality in the productive line for the manufacture of cylindrical and conical filters at Al-Zawraa General Company and the line of auto assembly, Saiba (Tiba) type in the General Company for automotive industry. as well as non-adoption of modern and developing techniques in the field of quality which led to the increase in the number of defective products in addition to the diversity of defects types. The target of research is to reveal the impact of using (Six Sigma) Technique and (Taguchi) function in the improving of production processes in the abovementioned companies; as well as to reveal the differences in the level of improving of production process, and determining the reasons that leading for deviations in production processes which participate in reducing the level of quality and develop appropriate solutions; after determining the current level of quality for both companies and the mechanisms used in measurement and quality control for both companies. The research reached a number of results, the most important of which is the possibility of applying Six Sigma in the two lines of the subject of research and giving good results for improvement. The fourth level of Sigma was reached after the third level and the number of defects was reduced; as well as research reached to determine the possibility of applying the Taguchi function - design experiments in the assembly line, Because of the lack of study able levels. Therefore, the loss function of Taguchi was applied instead. The most important conclusion was that the use of Six Sigma in the manufacturing and assembly lines is more efficient than Taguchi, and the lack of documentation of data for inspection by the quality control department of the two research groups, To identify the causes and problems that are repeated, analyzed and work on the treatment, and the methods of work that are applied both in the manufacturing line or in the assembly line is traditional not keeping pace with developments in the production and manufacturing processes, and the weak of performance of some employees due to lack of training courses and lack of experience and skill. The research produced a set of recommendations, the most important of which are: The use of modern technologies for quality and application for improvements, especially Six Sigma, which it is possible to apply in both types of production lines. Establish training courses for the employees to improve the work method and develop it and raise their achievement rates to improve the efficiency of the completion of the work.